Enhancing 4Cs Skills of Secondary School Students Using Project-Based Learning - Ruambhorn Somphol,; Anucha Pimsak,; Wisarut Payoungkiattikun,; Chulida Hemtasin, (Journal of Educational Issues, 2024)
The purposes of this research were to create project-based learning (PjBL) activities and to improve the students’ 4Cs skills using PjBL. The 4Cs of the learning skills assessment test and a record of student behavior serve as research tools. The mean and percentage are the statistics that were employed in the study. The results demonstrate that 1) students possess the 4Cs skills that passed the 70% criteria: communication skills (83.33%), critical thinking skills (70.83%), creativity skills (80.56%), and collaboration skills (85.42%). The examination of PjBL methodologies, with strongly suitable from three experts, includes step 1. Compose, step 2. Clarify, step 3. Comprehend, and step 4. Come Together.